2019
DOI: 10.1002/aqc.3143
|View full text |Cite
|
Sign up to set email alerts
|

High mortality of adult female Magellanic penguins by gillnet fisheries in southern Brazil

Abstract: Bycatch in gillnet fisheries is one of the main threats to several penguin species. Magellanic penguins (Spheniscus magellanicus) are caught by gillnets during their wintering in southern Brazil. However, current information is based only on a small number of sets observed during a single fishing trip. This study assesses bycatch rates of bottom and drift gillnets operating in southern Brazil, and describes the sex and age classes of individuals captured. In 80 bottom gillnet sets, 33 penguins were captured (8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 53 publications
(105 reference statements)
1
4
0
1
Order By: Relevance
“…The age groups described in previous reports of penguin bycatch in Brazil are contradictory. Vanstreels et al [22] and the present study reported mostly juveniles, respectively, 100 and 95%, while Cardoso et al [9], Marques et al, 2018 [10], and Fogliarini et al, 2019 [11] identified mostly adults (respectively, 81, 77 and 53%).…”
Section: Hepatic Hemosiderosis 10%supporting
confidence: 45%
See 1 more Smart Citation
“…The age groups described in previous reports of penguin bycatch in Brazil are contradictory. Vanstreels et al [22] and the present study reported mostly juveniles, respectively, 100 and 95%, while Cardoso et al [9], Marques et al, 2018 [10], and Fogliarini et al, 2019 [11] identified mostly adults (respectively, 81, 77 and 53%).…”
Section: Hepatic Hemosiderosis 10%supporting
confidence: 45%
“…Their potential impact in regards to bycatch may not be comparable with fishing nets used by commercial fisheries (e.g., longer and used offshore); however, gillnets are still a threat to penguins. Previous reports evidenced the gillnet bycatch of a large number of penguins in southern Brazil [8][9][10][11]; nonetheless, these studies did not perform complete postmortem examinations.…”
Section: Discussionmentioning
confidence: 99%
“…Fisheries by-catch mortality has been documented for Magellanic penguins all along its distributional range, especially in areas of high fishing effort during the autumn and winter periods off the coast of Argentina (e.g., [20][21][22]. Also, a female-biased mortality was found in carcasses of Magellanic penguins' overwintering grounds in southern Brazil among individuals died by starvation [23], and a female-biased mortality in by-catch of gillnet fisheries [24]. In northern Patagonia, a study reported that the non-breeding-season survival of females was lower than in males, thereby influencing population growth rate [25].…”
Section: Introductionmentioning
confidence: 99%
“…The current situation of overfishing for several artisanal fishing resources in the PLE, as demonstrated by this study, and for industrial resources in the coastal region as demonstrated by Haimovici and Cardoso (2016a), requires the attention of fishery managers. However, there is a clear lack of proper management measures or enforcement in southern Brazil, as several threatened marine megafauna species are killed annually in high numbers and most of the fish resources are overexploited (Fogliarini, Bugoni, Haimovici, Secchi, & Cardoso, 2019;Haimovici & Cardoso, 2016b;Prado, Mattos, Silva, & Secchi, 2016, this study). From a governance context of lack of enforcement or ineffective management or conservation strategies, Dowling et al (2016)…”
Section: Discussionmentioning
confidence: 83%